Educação física escolar: analisando o discurso e a ação docente - Fiorante, Flávia Baccin [UNESP]; Simões, Regina; Muzzeti, Luci Regina [UNESP]; Inforsato, Cassiano Ferreira; Inforsato, Edson do Carmo [UNESP] (My University, 2010)
Facing the mechanical model that dominated the schools from the end of the 19th century to the 1970s, new movements for the Physical Education emerged during the 1980s. These movements aimed at breaking up with the military concept of sport that reigned so far. This way we assign a historical period marked by significant transformations in Brazilian Physical Education, especially in school, and they are related to the raise of new school proposals, such as: the developmentist, the constructivist and the critical-overcomer. All this considered, the present paper aims at analyzing if these tendencies really influenced the pedagogical practice of a group of Physical Education teachers in public schools of Serra Negra, SP.

Frente ao modelo mecanicista que imperou do final do século XIX até final dos anos 70 do século XX, surgem, na década de 80, novos movimentos para a Educação Física Escolar. Estes tiveram como meta tentar romper com o eixo militarista e esportivista que vigorava até então. Diante desse pressuposto, assinala-se um período histórico marcado por significativas transformações na Educação Física Brasileira, em especial na escola, as quais estão relacionadas com o aparecimento de novas propostas para a Educação Física Escolar. São elas: a desenvolvimentista, a construtivista e a crítico-superadora. Diante dessas considerações, objetiva-se, neste trabalho, analisar se estas tendências refletiram ou não na prática pedagógica de um grupo de professores de Educação Física da 1a à 4a série das escolas estaduais da cidade de Serra Negra-SP.
Keywords: School; Tendencies; Physical education teaching; Pedagogical practice; Escola; Tendências; Ensino de Educação Física; Prática pedagógica